Inclusive Growth or Economic Exclusion? The Effect of Indonesia’s Investment Policies on Marginalized Communities (Indonesian Economic Justice Review, 2025)
This paper critically examines the impact of Indonesia’s investment policies on marginalized communities, particularly ethnic minorities, rural populations, and low-income groups. While Indonesia has implemented various investment policies to attract foreign direct investment (FDI) and stimulate economic growth, these policies have often been criticized for exacerbating social inequalities and failing to deliver inclusive growth. The study analyzes the role of government policies in shaping the distribution of economic benefits, particularly in relation to infrastructure projects, extractive industries, and urban development. By focusing on marginalized communities, such as the indigenous peoples of Papua and rural farmers in Java, the paper explores how large-scale investments have led to displacement, labor exploitation, and environmental degradation, often at the expense of local communities. The paper evaluates whether the benefits of FDI and economic growth are distributed equitably across society or if they mainly accrue to urban elites and multinational corporations. It also critiques the lack of safeguards in investment policies to protect marginalized groups from economic exclusion. The paper concludes with policy recommendations for fostering more inclusive economic growth, including strengthening community participation in development decisions, implementing better labor protections, and ensuring that investments prioritize long-term social and environmental sustainability.